2005
DOI: 10.1002/ppul.20289
|View full text |Cite
|
Sign up to set email alerts
|

Protein Oxidation by Chronic Pulmonary Diseases in Children

Abstract: Summary. The oxidation of proteins may play an important role in the pathogenesis of chronic inflammatory lung diseases, and may contribute to lung damage. However, the extent of oxidation and the distribution among proteins are not known for most pediatric lung diseases. In this work, protein oxidation was assessed as protein carbonyls. Bronchoalveolar lavages (BAL) from children with chronic lung diseases were investigated by dot-blot assay for content and for pattern of distribution of oxidized proteins by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Most of the proteins undergoing significant increases in oxidation had decreases or very modest increases in levels of expression between young adults and aged rats. The susceptibility of some of these BAL proteins to oxidation has been reported previously in humans (53). We speculate that the increased oxidation of these proteins results in functional deficits in the aged rats.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Most of the proteins undergoing significant increases in oxidation had decreases or very modest increases in levels of expression between young adults and aged rats. The susceptibility of some of these BAL proteins to oxidation has been reported previously in humans (53). We speculate that the increased oxidation of these proteins results in functional deficits in the aged rats.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies also have examined the carbonylation of BAL proteins in various diseases (47,53,54). However, no previous studies have examined changes in BAL protein expression or carbonylation with age.…”
Section: Ammentioning
confidence: 99%
“…A number of studies have shown that oxidation of SP-A by ozone impairs many aspects of SP-A function including decreased ability to interact with alveolar macrophages [15], to stimulate cytokine production by THP-1 cells [16 -17] to inhibit phosphatidylcholine (PC) and surfactant secretion by type II cells [18] and to stimulate TNF-a production by THP-1 cells in the presence of bleomycin [19]. In general, it has been found that SP-A was one of the most frequently oxidized lung proteins in children with chronic pulmonary diseases [20] as well as in patients with cystic fibrosis [21].…”
Section: Introductionmentioning
confidence: 99%
“…These triggers were severe gastro-intestinal reflux and pulmonary microaspiration, which were associated with declining lung function in infants and children [17], and reactive oxygen species-induced damage probably due to the depletion of glutathione, the major component of cell defences against oxidative injury, in the epithelial lining fluid and plasma of adults with CF [18][19][20].…”
Section: Lung Damage In Cystic Fibrosismentioning
confidence: 99%